The Correlation between Internet Addiction and Anxiety Level among Medical Students at Medicine Study Program of Medicine Faculty, Mulawarman University - Meilinda Meilinda; Jaya Mualimin; Ika Fikriah (Fakultas Kedokteran, 2022)
AbstrakLatar Belakang : Pengguna internet yang terus bertambah berpotensi mendatangkan permasalahan baru bagi penggunanya yaitu suatu fenomena yang disebut adiksi internet. Adiksi internet adalah penggunaan internet yang berlebihan dan bisa berdampak negatif pada kondisi psikologi seseorang salah satunya berupa kecemasan. Tujuan Penelitian : Untuk mengetahui hubungan antara adiksi internet dengan tingkat kecemasan pada mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Mulawarman. Metode : Penelitian ini merupakan penelitian observasional analitik dengan desain cross-sectional. Subjek pada penelitian ini sebanyak 83 orang dipilih dengan metode stratified random sampling. Instrumen yang digunakan adalah Internet Addiction test (IAT) dan Beck Anxiety Inventory (BAI) disebarkan melalui google form. 83 responden yang terdiri dari 28 mahasiswa laki-laki dan 55 mahasiswa perempuan. Hasil : Didapatkan hasil 15 (18,1%) responden tidak mengalami adiksi internet, 49 (72,1%) responden mengalami adiksi internet tingkat ringan, 18 (26,5%) mengalami adiksi internet tingkat sedang, dan 1 (1,5%) mengalami adiksi internet tingkat berat. Sedangkan untuk kecemasan sebanyak 33 (39,8%) responden tidak mengalami kecemasan, 38 (76%) kecemasan ringan, 11 (22%) kecemasan sedang, dan 1 (2%) kecemasan berat. Hasil analisis bivariat dengan uji Chi Square tidak terdapat hubungan antara adiksi internet dengan tingkat kecemasan pada mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Mulawarman (p value > 0,005; p= 0,077).Kata Kunci: adiksi internet, kecemasan, mahasiswa AbstractBackground: A growing number of internet users may potentially raise a problem called a phenomenon of internet addiction. Internet addiction is generally defined as excessive internet use and gives negative effects on people’s psychological condition, one of which is anxiety. Research Objectives: To know the correlation between internet addiction and anxiety level among medical students at Medicine Study Program of Medicine Faculty, Mulawarman University. Methods: This was an analytical observational research with cross-sectional design. There were 83 research subjects consisting of 28 male and 55 female students selected using stratified random sampling method. Two instruments, Internet Addiction test (IAT) and Beck Anxiety Inventory (BAI), were distributed through Google Form. Result: The findings revealed that 15 (19.1%) respondents experienced the absence of internet addiction, 49 (72,1%) respondents experienced low level of internet addiction, 8 (26,5%) respondents experienced moderate level of internet addiction, and 1 (1.5%) student experienced severe level of internet addiction. In addition, students’ anxiety levels among students were 33 (39,8%) respondents with zero anxiety level, 38 (76%) respondents with low anxiety level, 11 (22%) respondents with moderate anxiety level, and 1 (2%) student with high anxiety level. The result of bivariate analysis using Chi Square test showed that there was no correlation between internet addiction and anxiety level among medical students at Medicine Study Program of Medicine Faculty, Mulawarman University (p value > 0,005; p= 0,077).Keywords: Internet addiction, anxiety, student